Elastic compressible energy storage devices from ice templated polymer gels treated with polyphenols - Das, Chayanika; Chatterjee, Soumyajyoti; Kumaraswamy, Guruswamy; Krishnarnoorthy, Kothandam (Journal of Physical Chemistry C, 2017)
Design and fabrication of rechargeable energy storage devices that are robust to mechanical deformation is essential for wearable electronics. We report the preparation of compressible supercapacitors that retain their specific capacitance after large compression and that recover elastically after at least a hundred compression expansion cycles. Compressible supercapacitors are prepared using a facile, scalable method that readily yields centimeter-scale macroporous objects. We ice template a solution of polyethylenimine in green tea extract to prepare a macroporous cross-linked polymer gel (PG) whose walls are impregnated with green tea derived polyphenols. As the PG is insulating, we impart conductivity by deposition of gold on it. Gold deposition is done in two steps: first, silver nanoparticles are formed on the PG walls by in situ reduction by polyphenols and then gold films are deposited on these walls. Gold coated PGs (GPGs) were used as electrodes to deposit poly(3,4-ethylenedioxythiophene) as a pseudocapacitive material. The specific capacitance of PEDOT coated GPGs (PGPG) was found to be 253 F/g at 1 A/g. PGPG could be compressed and expanded over a hundred cycles without any suffering mechanical failure or loss of capacitative performance. The capacitance was found to be 243 F/g upon compressing the device to 25% of its original size (viz. compressive strain = 75%). Thus, even large compression does not affect the device performance. This device shows power and energy densities of 2715 W/kg and 22 Wh/kg, respectively, in the uncompressed state. The macroporous nature of PGPG makes it possible to fill the PGPG pores with gel electrolyte. We report that the gel electrolyte filled supercapacitor exhibited a specific capacitance of 200 F/g, which increased by 4% upon 75% compression.